Rapid Synthesis of High‐Entropy Oxide Microparticles. Issue 11 (20th January 2022) - Dong, Qi; Hong, Min; Gao, Jinlong; Li, Tangyuan; Cui, Mingjin; Li, Shuke; Qiao, Haiyu; Brozena, Alexandra H.; Yao, Yonggang; Wang, Xizheng; Chen, Gang; Luo, Jian; et al.
Abstract: High‐entropy nanoparticles have received notable attention due to their tunable properties and broad material space. However, these nanoparticles are not suitable for certain applications (e.g., battery electrodes), where their microparticle (submicron to micron) counterparts are more preferred. Conventional methods used for synthesizing high‐entropy nanoparticles often involve various ultrafast shock processes. To increase the size thereby achieving high‐entropy microparticles, longer reaction time (e.g., heating duration) is usually used, which may also lead to undesired particle overgrowth or even densified microstructures. In this work, an approach based on Joule heating for synthesizing high‐entropy oxide (HEO) microparticles with uniform elemental distribution is reported. In particular, two key synthesis conditions are identified to achieve high‐quality HEO microparticles: 1) the precursors need to be loosely packed to avoid densification; 2) the heating time needs to be accurately controlled to tens of seconds instead of using milliseconds (thermal shock) that leads to nanoparticles or longer heating duration that forms bulk structures. The utility of the synthesized HEO microparticles for a range of applications, including high‐performance Li‐ion battery anode and water oxidation catalyst. This study opens up a new door toward synthesizing high‐entropy microparticles with high quality and broad material space. Abstract : A high‐temperature rapid heating approach for the synthesis of high‐entropy oxide (HEO) microparticles with uniform elemental distribution and a variety of compositions is reported. With a simple Joule‐heated carbon‐based reactor, the authors are able to obtain HEO microparticles by using a high temperature of ≈1500 K and accurately adjusting the heating time to tens of seconds.